Penciling a triboelectric nanogenerator on paper for autonomous power MEMS applications. (March 2017) - Zhang, Xiao-Sheng; Su, Meng; Brugger, Jürgen; Kim, Beomjoon
Abstract: Triboelectric nanogenerator (TENG) has proven to be a robust power source to efficiently convert ambient mechanical energy into electricity. It experienced substantial growth in the past years owing to its appealing features that make it superior than other self-powering principles. In particular, it excels in high output performance, sustainability in powering capability, as well as the ability to work completely autonomously. However, in order for TENG to make a real impact for societal applications, further improvements towards cost-effective TENG are required, in particular by exploring new inexpensive electrification materials and by simplifying the manufacture procedure. In this work, we present a paper-TENG completely prepared using cost efficient, commercially available commodity materials, such as paper cards, Teflon tape, and graphite pencil. Here, paper was firstly utilized as both supporting structure and functionally triboelectric pair simultaneously, which is widely available at low cost, and in addition, to our advantage, it has a considerably high ability to lose electrons during triboelectrification. As scalable fabrication, we implemented a single step using sandpaper imprinting to increase effective friction area and simple electrode fabrication by means of a graphite pencil. These two technical innovations were systematically studied as to the micro/nano-textured surfaces and conductive electrodes. The electrical properties of fabricated paper TENGs were comprehensively investigated and proved to be a usable power source by using a well-designed vibration platform and practical body motion, respectively. The fabricated paper TENG was successfully utilized to move liquid droplets in designated directions via electro-wetting. This new implementation of controlled droplet manipulation shows an attractive potential of TENG's applications in multidisciplinary fields, such as inkjet printing and lab-on-chip biomedical micro/nano-systems. Graphical abstract: Highlights: A paper-TENG completely prepared using cost efficient, commercially available commodity materials, is proposed. Household material, i.e. common paper card, is employed for the first time as an electrification material to construct TENG. Single-step processes, i.e. penciling and imprinting, are developed to significantly simplify the manufacturing of TENG. First TENG demonstration realizing controlled manipulation of droplet, which shows an attractive potential in various fields.